Legal Aspects of Agreements in Franchise Business and Characteristics of Franchise Business in Indonesia - Ilham, Rianza Naufalfalah; Urbaniasi, Urbaniasi (CV. Rayyan Dwi Bharata, 2023)
The many human needs and interests give rise to various kinds of disputes that can occur because one or more parties feel aggrieved. So that these parties feel safe in fulfilling their interests, one of the precautions that can be taken is to form an agreement so as not to disturb the balance of the order of people's lives. Agreements have a very important role in the business realm. This role can be seen from the increasing number of trade transactions that have now penetrated across borders. These trade transactions are often poured into an agreement or better known in the business world as a contract. The franchise business thrives in Indonesia, both foreign and local.